Meningkatkan hasil belajar matematika melalui penerapan model contextual teaching and learning pada era new normal - Hasan Hasan (Indonesian Journal of Educational Development, 2021)
The purpose of this study was to find out how to improve student learning outcomes in statistical data centering material in the new normal era with a learning model using the Contextual Teaching and Learning (CTL) model. This research is a classroom action research (PTK) which is conducted in 2 cycles, each of which goes through 4 stages, namely, planning, implementing, observing, and reflecting. The research subjects were students of class XII IPA at SMA Negeri 1 Pringgasela in the 2020/2021 school year. The object of research is the result of learning mathematics. This action research is said to be successful if the average value of mathematics learning outcomes is at least the KKM value = 70. Mathematics learning outcomes data were collected using test instruments. Data were analyzed descriptively qualitatively. The results showed that the mean value of pre-cycle learning outcomes was 63.78. After the action research was carried out, the class mean value in the first cycle increased to 68.63, while in the second cycle the class mean value had succeeded in achieving the success criteria of 72.36. Therefore, it can be concluded that the use of the Contextual Teaching and Learning (CTL) learning model assisted by leaf media in the new normal era can improve student mathematics learning outcomes in class XII IPA 1 SMA Negeri 1 Pringgasela in the 2020/2021 school year. Tujuan penelitian ini untuk mengetahui bagaimana peningkatan hasil belajar siswa pada materi pemusatan data statistik di era new normal dengan model pembelajaran menggunakan model Contextual Teaching and Learning (CTL). Penelitian merupakan penelitian tindakan kelas (PTK) yang dilakukan dalam 2 siklus yang masing-masing melalui 4 tahapan yaitu, perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas XII IPA SMA Negeri 1 Pringgasela tahun ajaran 2020/2021. Objek penelitian dalah hasil belajar matematika. Penelitian tindakan ini dikatakan berhasil bila nilai rerata hasil belajar matematika minimal sebesar nilai KKM=70. Data hasil belajar matematika dikumpulkan menggunakan instrumen tes. Data dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa nilai rerata hasil belajar prasiklus sebesar 63,78. Setelah dilakukan penelitian tindakan, nilai rerata kelas pada siklus I meningkat menjadi 68,63 sedangkan pada siklus II nilai rerata kelas telah berhasil mencapai kriteria keberhasilan sebesar 72,36. Oleh karena itu, dapat disimpulkan bahwa penggunaan model pembelajaran Contextual Teaching and Learning (CTL) dibantu media daun di era new normal dapat meningkatkan hasil belajar matematika siswa pada kelas XII IPA 1 SMA Negeri 1 Pringgasela tahun pelajaran 2020/2021.